2016
DOI: 10.3762/bjnano.7.182
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of luminescent organic dots by thermolysis of citric acid in urea melt, and their use for cell staining and polyelectrolyte microcapsule labelling

Abstract: Luminescent organic dots (O-dots) were synthesized via a one-pot, solvent-free thermolysis of citric acid in urea melt. The influence of the ratio of the precursors and the duration of the process on the properties of the O-dots was established and a mechanism of their formation was hypothesized. The multicolour luminescence tunability and toxicity of synthesized O-dots were extensively studied. The possible applications of O-dots for alive/fixed cell staining and labelling of layer-by-layer polyelectrolyte mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 62 publications
2
38
0
Order By: Relevance
“…The above highlights the applicability of the CND-based complex as a ratiometric fluorescent imaging agent for targeted endogenous and exogenous hydrogen peroxide in living cells. In another study, Zholobak et al prepared CNDs by melting citric acid and urea [90]. They incubated diploid epithelial swine testicular cells with the CNDs and found that although the CNDs cause no toxicity to the cells, they inhibit the activity of NADP-H-dependent oxidoreductase enzymes.…”
Section: Target-specific Imaging Applications For Eukaryotic Cellsmentioning
confidence: 99%
“…The above highlights the applicability of the CND-based complex as a ratiometric fluorescent imaging agent for targeted endogenous and exogenous hydrogen peroxide in living cells. In another study, Zholobak et al prepared CNDs by melting citric acid and urea [90]. They incubated diploid epithelial swine testicular cells with the CNDs and found that although the CNDs cause no toxicity to the cells, they inhibit the activity of NADP-H-dependent oxidoreductase enzymes.…”
Section: Target-specific Imaging Applications For Eukaryotic Cellsmentioning
confidence: 99%
“…[56] Zholobak also applied CDs synthesized from CA and urea for live/fixed diploid epithelial swine testicular cell line (ST-cells) staining. [74] Furthermore, in vivo bioimaging was also conducted with citrate-based CDs. Goh et al utilized citrate-based CDs for in vivo real time bioimaging of target-specific delivery of hyaluronic acid (HA) derivatives.…”
Section: Citrate-based Carbon Dots (Cds)mentioning
confidence: 99%
“…1d). Because the UV-Vis absorption of citrazinic acid is characterised by a main band peaking around 340 nm, this molecule and its derivates should be the primary source of the fluorescence at around 450 nm 1,7,13 ( Supplementary Information, Fig. S1).…”
mentioning
confidence: 99%